Status Hukum Wasiat Beda Agama Ditinjau Dari Fiqih Syafi’iyyah Dan Kompilasi Hukum Islam (KHI) - Alfian Fauzan (Universitas Maritim AMNI Semarang, 2023)
This will system has been running since ancient times, not only the Islamic religion regulates it, but every community has an understanding of wills. A will is a gift of property from a person to another person or to several people whose implementation is after the person's death. The type of research used is library research, because the study is focused on library materials by tracing and examining academic standard literature. Methods of data collection in the form of books, journals, and Islamic law compilation regulations (KHI). The results of the study show that Syafiiyah's legal view of wills applies to anyone who is not an heir. However, there are limitations to giving the will. Where, a person is only entitled to bequeath a small portion of his property. This is intended so that the will does not harm the heirs left behind. Meanwhile, the pillars in the will in the view of fiwih Syafiiyah are the person who inherits, the person who is inherited, the will and the presence of sighar or consent qabul. Whereas the will according to positive law states that the existence of article 195 of the Compilation of Islamic Law (KHI) can be realized in the current Indonesian context because in general the existence of the Compilation of Islamic Law (KHI) includes article 195.